Reconstruction of the Technical Condition of Concrete Airfield Pavements with the Use of Prefabricated Slab Technology - Świerzewski, Bartosz; Wesołowski, Mariusz (IOP conference series. Materials Science and Engineering, 2020)
The rapidly growing civil aviation industry is primarily an increase in the number of air operations, both in passenger and cargo traffic. This leads to an increase in the impact of aircraft on airfield pavement structures and, consequently, to an intensive operation process. Concrete airfield pavements occurring at airports in Poland, but also around the world, cover a wide spectrum, starting from newly built surfaces, used ones as well as those that are subject to renovation. Particular attention should be paid to pavements in the process of operation and pavements which age exceeds the designed useful life and which are already subject to renovation works. Basic types of failures can be identified on concrete airfield pavements including surface failures (e.g. spalling, cracks), local failures (e.g. pop-outs, corner cracks), linear failures (e.g. meander cracks, decrements of the pourable sealing compound in expansion gaps). Currently, where in many cases there is an urgent need to repair damaged pavement, companies and organizations responsible for road/airport construction are looking for new and innovative technologies, including prefabricated concrete pavement technologies, which can ensure effective repairs in a very short time, without closing the given lane or the entire airport. Due to the fact that the age of currently used airfield concrete pavements in Poland often exceeds 30 years, it became necessary to search for effective and fast technologies to improve their technical condition. This article summarizes the current state of knowledge in the field of existing prefabricated concrete technologies used at airports in Poland and worldwide. In addition, an innovative technology of using a prefabricated concrete slab has been described, intended for reconstruction of damaged, local airfield pavements in Poland, which were qualified for renovation due to the direct threat to the safety of aircraft operations. The technology guarantees the reconstruction and even improvement of the load capacity of the replaced airfield panels, which was confirmed during laboratory and field tests and verified practically in the process of real operation by air traffic. In addition, the concept of further research on the development of this technology based on cooperation with neighbouring panels using dowel joints will be presented.